Re-thinking reablement strategies for older adults in residential aged care: a scoping review - Lucy K. Lewis (BMC, 2021)
Abstract Background The number of older adults in residential aged care is increasing. Aged care residents have been shown to spend most of the day sedentary and have many co-morbidities. This review aimed to systematically explore the effectiveness of reablement strategies in residential aged care for older adults’ physical function, quality of life and mental health, the features of effective interventions and feasibility (compliance, acceptability, adverse events and cost effectiveness). Method This scoping review was undertaken according to PRISMA guidelines (extension for scoping reviews). Five e-databases (Medline, Embase, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and CINAHL) were searched from 2010 onwards. Randomised controlled trials investigating reablement strategies addressing physical deconditioning for older adults (mean age ≥ 65 yrs) in residential aged care on physical function, quality of life or mental health were included. Feasibility of the interventions (compliance, acceptability, satisfaction, adverse events and cost effectiveness) was explored. Results Five thousand six hundred thirty-one citations were retrieved, and 63 studies included. Sample sizes ranged from 15 to 322 and intervention duration from one to 12 months. Exercise sessions were most often conducted two to three times per week (44 studies) and physiotherapist-led (27 studies). Interventions were predominately multi-component (28 studies, combinations of strength, balance, aerobic, functional exercises). Five interventions used technology. 60% of studies measuring physical function reported significant improvement in the intervention versus control, 40% of studies measuring quality of life reported significant improvements in favour of the intervention, and 26% of studies measuring mental health reported significant intervention benefits. Over half of the studies measured compliance and adverse events, four measured acceptability and none reported cost effectiveness. Conclusions There has been a research surge investigating reablement strategies in residential aged care with wide variability in the types and features of strategies and outcome measures. Few studies have measured acceptability, or cost effectiveness. Exploration of core outcomes, mapping stakeholders and co-designing a scalable intervention is warranted. Trial registration Prospectively registered review protocol (Open Science Framework: DOI https://doi.org/10.17605/OSF.IO/7NX9M ).